2012
DOI: 10.3892/mmr.2015.4479
|View full text |Cite
|
Sign up to set email alerts
|

CXC195 induces apoptosis and endoplastic reticulum stress in human hepatocellular carcinoma cells by inhibiting the PI3K/Akt/mTOR signaling pathway

Abstract: CXC195 exhibits strong protective effects against neuronal apoptosis by exerting antioxidant activity. However, the pharmacological function of CXC195 in cancer remains to be elucidated. The present study demonstrated that CXC195 exhibited significant cytotoxic effects, and induced cell cycle arrest and apoptosis in HepG2 human hepatocellular carcinoma (HCC) cell lines. Following treatment of HepG2 cells with 150 µΜ CXC195 for 24 , cell viability and the apoptotic rate were assessed using an MTT assay and Anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In this sense, ERS may induce autophagy and apoptosis via the suppression of mTOR (26). Chen et al reported similar results to the present study and identified a causal relationship between ERS and autophagy-mediated apoptosis in human hepatocellular carcinoma cell lines with the aid of PI3K/AKT/mTOR signaling pathway inhibition (27).…”
Section: Discussionsupporting
confidence: 89%
“…In this sense, ERS may induce autophagy and apoptosis via the suppression of mTOR (26). Chen et al reported similar results to the present study and identified a causal relationship between ERS and autophagy-mediated apoptosis in human hepatocellular carcinoma cell lines with the aid of PI3K/AKT/mTOR signaling pathway inhibition (27).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies demonstrated that mTOR pathways, including pRPS6, p-AKT, IGF-1R and RICTOR are up-regulated in 40-50% of HCCs, highlighting its importance in HCC [26]. Additionally, inhibition of mTOR signaling has been reported to sensitize tumor cells to apoptosis induced by several anticancer agents [27,28]. Here we find that the upregulation of miR-223 could suppress the expression of its target gene Rab1, which can inhibit mTOR pathway activation, and leads to enhancement of miR-223-regulated cell death and apoptosis in HCC cells.…”
Section: Mtt Assays Showed That Mir-223 Significantly Suppressed Prolmentioning
confidence: 99%
“…Numerous lines of evidence have shown that ER stress (ERS) can up-regulate DR5 expression, and this process plays an important role in the initiation of apoptosis of human cancer cells [ 24 , 25 ]. Additionally, activation of ER stress can inhibit the AKT/mTOR signaling pathway in numerous types of tumor cells [ 26 28 ]. Mammalian target of rapamycin (mTOR) is commonly activated in multiple tumors and forms two multiprotein complexes, mTORC1 and mTORC2, that control various cellular processes, including cell proliferation, metabolism, invasion, and autophagy [ 29 33 ].…”
Section: Introductionmentioning
confidence: 99%